2005
DOI: 10.1097/01.mlg.0000154731.08410.b8
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mastoid Air Cell System in Children Treated With Ventilation Tubes for Early-Onset Otitis Media: A Prospective Radiographic 5-Year Follow-Up Study

Abstract: The genetically determined development of mastoid air cell system is arrested in varying degree by environmental factors, particularly by an early onset of otitis media, a long-standing disease, and an unfavorable otological outcome. On the other hand, poor pneumatization seems to be a risk factor for chronic and recurrent infections and, ultimately, for a deficient otological outcome. However, in a vast majority of patients, this untoward development may be reversed by an early and, if needed, repeated tympan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 18 publications
3
47
2
1
Order By: Relevance
“…gases characterized by perfusion limited transmucosal exchange). Previously, a significant increase in ME pressure was reported for anesthetized patients breathing gas mixtures that included N 2 O [7,30] and one study reported paired data for pneumatized MACS area and the rate of change in ME pressure during 50% N 2 O breathing in adult subjects [18]. Like N 2 , N 2 O is an inert gas whose rate of exchange across the ME mucosa is primarily perfusion limited [28].…”
Section: Hypothesis Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…gases characterized by perfusion limited transmucosal exchange). Previously, a significant increase in ME pressure was reported for anesthetized patients breathing gas mixtures that included N 2 O [7,30] and one study reported paired data for pneumatized MACS area and the rate of change in ME pressure during 50% N 2 O breathing in adult subjects [18]. Like N 2 , N 2 O is an inert gas whose rate of exchange across the ME mucosa is primarily perfusion limited [28].…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Developmentally, the MACS shows an age-related increase in volume to exceed that of the tympanum by fold magnitudes in adults. Previous studies reported that children with small MACS volume had significantly more episodes of otitis media and otitis media episodes of longer duration when compared to age-matched controls with large MACS volume, and other studies reported that adults with small MACS volume were at higher risk for otitis media during upper respiratory infections when compared to those with large MACS volume [3][4][5][6][7]. This linkage between MACS size and predisposition to middle ear (ME) disease has been interpreted as evidencing directional causality with either small MACS volume predisposing to otitis media or, alternatively, with otitis media stunting the expansion of MACS volume during growth [2,4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in overall size may drive the noted variation seen in the 9-to-18 age group, which represents the greatest age span within the sample, and possibly the greatest differences in overall temporal bone size. Early exposure to otitis media may also result in disparate adult size of the pneumatized spaces, because significant variability in size of pneumatized spaces is evident in clinical samples of individuals with otitis media (e.g., Valtonen et al, 2005). Careful selection of apparently nondiseased individuals may not have been sufficient to prevent this situation, because one incident of otitis media can inhibit pneumatization (Caye-Thomasen et al, 1999).…”
Section: Changes In Surface Areas and Volumes During Ontogenymentioning
confidence: 99%
“…Up to date, there is considerable evidence to indicate that the genetically controlled normal mastoid pneumatization can be changed in varying degrees by postnatal environmental factors. [3][4][5] It has been studied if the paranasal sinus (PNS) could influence the degree of mastoid pneumatization postnatally. Its background is that PNSs drain backward from the superior and middle meatus to the nasopharynx, and the ventilation/drainage outlet of the middle ear-mastoid pneumatization systems opens into the nasopharynx.…”
Section: Introductionmentioning
confidence: 99%